Multidisciplinary care of pediatric obesity and its impact on sleep: a review - Inja, Ravali; Cielo, Christopher (Frontiers in Sleep, 2026)
Pediatric obesity has emerged as a significant global health issue with multifaceted consequences, including its impact on sleep health. Obstructive sleep apnea (OSA) and obesity hypoventilation syndrome (OHS) are among the serious sleep-related comorbidities in obese children, contributing to impaired quality of life, cognitive deficits, and cardiovascular risks. These conditions frequently coexist with other obesity-related complications such as insulin resistance, type 2 diabetes, hypertension, and non-alcoholic fatty liver disease (NAFLD). This review explores the importance of multidisciplinary care in addressing pediatric obesity, emphasizing early diagnosis, nutritional counseling, physical activity interventions, psychological support, and pharmacologic therapies such as glucagon-like peptide-1 (GLP-1) receptor agonists. The role of global trends, academic performance, and wellbeing clinics are also discussed. Although promising, the use of GLP-1s and surgical interventions in pediatrics remains constrained by limited data, particularly concerning their impact on sleep disorders. Further research is essential to clarify the long-term effects of GLP-1 receptor agonists and bariatric surgery not only on obesity and sleep-related comorbidities such as OSA and OHS, but also on cognitive function, psychosocial wellbeing, and overall health outcomes—thereby informing evidence-based, multidisciplinary approaches to pediatric obesity management.